HUBUNGAN POLA ASUH ORANG TUA DAN KARIES TERHADAP OHRQoL PADA ANAK USIA PRASEKOLAH - I Made Yudha Dharmawan; R. Harry Dharmawan Setyawardhana; Muhammad Yanuar Ichrom Nahzi; Diana Wibowo; Ika Kusuma Wardani (Universitas Lambung Mangkurat, 2024)
Background: Children's dental and oral health problems are caused by many factors including parenting style which has a major influence on children's health and development. In Tanah Bumbu District, children aged over 3 years had a proportion of 50.74% with broken teeth, cavities and pain. Dental caries can cause disruption of children's quality of life such as sleep disturbances, eating disorders, loss of concentration in learning, infections, and other dangerous cases in children. Objective: To determine the relationship between parenting style and caries towards OHRQoL in preschool-aged children in Sungai Loban District. Method: Analytic observational study with a cross sectional approach. The sampling technique of non-probability sampling uses quota sampling. The population is all kindergartens in Sungai Loban District, namely 23 kindergartens with 918 children. The minimum sample size was calculated using the correlational analytic formula and the results obtained were 40 respondents consisting of parents and children taken from 3 kindergartens, namely Harapan Bersama Kindergarten, Taman Sari Kindergarten and Tunas Dewata Kindergarten, Sungai Loban District. Results: Most parents' parenting style has a democratic pattern; the average def-t index is 5.5 and belongs to the high category. The results of the Spearman correlation test showed that there was not a relationship between parenting style and OHRQoL (p>0.05). The results of the Spearman correlation test analysis showed that there was a relationship between caries and OHRQoL (p<0.05). Conclusion: There is a relationship between parenting style and caries to OHRQoL in preschool-aged children in Kindergarten in Sungai Loban District.Keywords: Caries, OHRQoL, Parenting, Preschool children.